Preparation method and application of nano organic titanium polymer and titanium-based polymer alloy copolymer

Through the mechanochemical solid-liquid ball milling reaction method, high-quality nanoorgano-titanium polymer and titanium-based polymer alloy copolymer were synthesized, solving the problems of unreasonable raw material ratios and incomplete preparation methods in the existing technology, and achieving the efficient application of nanoorgano-titanium polymers in industrial anticorrosion coatings.

CN119708504AInactive Publication Date: 2025-03-28SHAANXI ZHIQIANG HEAVY DUTY MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411769379.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when preparing nanoorganic titanium polymers, the raw material ratio is unreasonable and the preparation method is incomplete, resulting in the low quality of the nanoorganic titanium polymers and cannot meet the expectations of industrial anti-corrosion.

Method used

The mechanical chemical solid-liquid ball milling reaction method is used to blend titanium metal fine powder with organic epoxy resin or other polymer resins, and nano-processing is carried out in a planetary ball milling reactor. Through the process of breaking chains and bonds, graft bonding and hybrid polymerization, high-quality nanoorganic titanium precursor polymer and titanium-based polymer alloy copolymer are synthesized.

Benefits of technology

The generated nanoorganic titanium polymer has super anticorrosion properties and is suitable for industrial heavy anticorrosion coatings, achieving high quality and stability that cannot be achieved in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708504A_ABST
    Figure CN119708504A_ABST
Patent Text Reader

Abstract

The invention discloses a nano organic titanium polymer and titanium-based polymer alloy copolymer as well as a preparation method and application thereof, and belongs to the technical field of material application. According to the invention, the defects in the prior art are overcome, titanium metal fine powder and organic epoxy resin or other polymer resin are blended, a nanocrystallization process is carried out in a planetary ball-milling reaction kettle, and complete chain and bond breaking, graft bonding and hybrid polymerization processes are carried out through a mechanochemical reaction, so that the titanium metal fine powder is obtained. According to the present invention, the nanometer organic titanium polymer and the titanium-based polymer alloy copolymer with the titanium element as the matrix are synthesized, the nanometer organic titanium polymer and the titanium-based polymer alloy copolymer are adopted as the matrix film forming material to be applied to the coating material, and the coating material can be widely used in the industrial heavy corrosion prevention field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material application, and particularly relates to a method for preparing a nano-organic titanium polymer and a titanium-based high molecular alloy copolymer and an application thereof in preparing coatings. Background Art

[0002] The standard electrode potential of titanium is very low (E = -1.63V), and the passivation potential is also low, so it is easy to passivate. At room temperature, a passivation film composed of oxides and nitrides is easily formed on the surface of titanium. It is very stable in the atmosphere and many corrosive media and has good corrosion resistance. In the atmosphere, seawater, chloride aqueous solution, oxidizing acid (nitric acid, chromic acid, etc.) and most organic acids, its corrosion resistance exceeds that of stainless steel; it is basically not corroded in seawater, so it is an ideal metal structural material in petrochemical and marine engineering. However, the manufacturing cost of metal titanium materials is high and the price is expensive. From the perspective of market application, it cannot be used on a large scale in engineering anti-corrosion applications. Since metal titanium has such good protective properties, can it be prepared into a low-cost coating and used in the field of industrial anti-corrosion in the form of a coating, which can not only give full play to the anti-corrosion properties of titanium metal, but also reduce the cost of use. Based on this concept, scientific research and engineering technicians in the corresponding field have carried out research and exploration, and have achieved some results so far.

[0003] Organic titanium polymer is a general term for a class of organic polymers containing titanium in their molecular structure. It is a class of organic metal polymers with side groups containing the structure of "-O-Ti-C-" and functional groups on the main chain. The chemical structure is as follows:

[0004]

[0005] Wherein R is an organic unit.

[0006] This type of organic titanium polymer was previously synthesized by thermochemical methods, but it is difficult to change the molecular structure of the synthesized product according to human design and create new structural products by thermochemical methods. The mechanochemical method breaks the conventional thermochemical tradition and can adjust the molecular structure according to human design to synthesize new materials.

[0007] CN106141164A discloses a method for preparing a titanium nanopolymer, but its raw material ratio is too general, lacks core raw materials, and cannot generate a stable nano-organic titanium polymer; CN111253835B discloses a nano-titanium alloy hybrid polymer and its preparation method and a nano-hybrid composite coating, but its process flow is imperfect, and the generated product is not a nano-organic titanium polymer, but a nano-titanium alloy hybrid, so the application effect of the nano-organic titanium polymer cannot be achieved. CN102585236B discloses a nano-organic titanium polymer and coating and its preparation method, but its raw material ratio is incomplete, especially the preparation method has basic defects, in addition to the production process There are hidden safety hazards, there are also problems such as low production efficiency and unstable product quality.

[0008] In summary, the common shortcomings of the prior art are that the raw materials and components for generating nano-organic titanium polymers are unreasonable, the preparation methods are incomplete and non-standard, and during the mechanochemical reaction, the reaction process of titanium metal and organic synthetic resin is incomplete during "chain breaking and bond breaking" and "graft bonding", and the nano-organic titanium polymers cannot be generated or the index parameters of the generated nano-organic titanium polymers are unstable and the quality is not high. Therefore, the application effect of the coating prepared with it as the film-forming matrix cannot meet the actual expectations of industrial corrosion protection. Summary of the invention

[0009] After more than 30 years of continuous research and exploration, the present invention overcomes the shortcomings of the prior art, blends titanium metal fine powder with organic epoxy resin or other polymer resin, performs nano-processing in a planetary ball mill reactor, and undergoes complete chain breaking, bond breaking, graft bonding and hybrid polymerization processes through mechanochemical solid-liquid ball milling reaction, synthesizing a nano-organic titanium precursor polymer (Nanoorganictitaniumprecursorpolyme) based on titanium element, referred to as nano-organic titanium polymer and titanium-based polymer alloy copolymer, and applies these as matrix film-forming materials to coatings. This type of polymer metamaterial, due to the change in the molecular structure of its elementary resin, also changes its physical properties, showing super strong anti-corrosion performance and a trend of multiple performance.

[0010] 1. Composition and preparation principle of nano-organic titanium polymer

[0011] Raw materials and ingredients:

[0012] 1. 50-200 parts of liquid low-viscosity epoxy resin or phenoxy resin (also known as polyphenol oxide resin);

[0013] 2. 200-400 parts of epoxy reactive diluent or phenoxy reactive diluent;

[0014] 3. 500-800 parts of titanium hydride powder;

[0015] 4. 50-150 parts of nano material dispersant;

[0016] 5. 20-50 parts of polymer toughening agent;

[0017] 6. 5-20 parts of coupling agent;

[0018] 7. 1 to 10 parts of functional additives;

[0019] 8. 0 to 10 parts of γ-phase nano-alumina or sodium hydrogen phthalate catalyst.

[0020] Preferably, the liquid low-viscosity epoxy resin described in 1 can be EP127, EP128, GT-807, DEN-431, etc.;

[0021] Preferably, the epoxy reactive diluent described in 2 can be a multifunctional glycidyl ether or ester reactive solvent, such as C12-14 alkyl glycidyl ether (AGE), XY-207 polypropylene glycol diglycidyl ether, 692 benzyl glycidyl ether, H61N-butyl glycidyl ether, H62 toluene glycidyl ether, H11 neodecanoic acid glycidyl ether, D-1301 trimethylolpropane triglycidyl ether; 801 tert-butyl glycidyl ester, 816 glycidyl ester, D-691 glycidyl ester, etc.

[0022] Preferably, the titanium hydride powder described in 3 is required to have a purity of ≥99.5% and an average particle size of ≤10 μm;

[0023] Preferably, the nanomaterial dispersant described in 4 can be in powder or liquid form and is required to be a small molecule carboxyl oligomer;

[0024] Preferably, the polymer toughening agent described in 5 can be liquid rubber, organic elastomer resin or polyphosphate, preferably liquid rubber;

[0025] Preferably, the coupling agent described in 6 can be a silane, titanate, aluminate or zirconate, preferably a silane or titanate coupling agent;

[0026] Preferably, the functional additives described in 7 include defoamers, leveling agents, anti-settling agents, and thickeners, which may be silicone, acrylic, or polyurethane additives;

[0027] Preferably, the catalyst γ-phase nano-alumina (γ-Al2O3) or sodium hydrogen phthalate (C8H7NaO4) described in 8 requires the purity of γ-phase nano-alumina to be ≥99.5%, D 90 =10~20nm.

[0028] Preferably, in 1-8, when 1-2 uses a liquid low-viscosity epoxy resin and an epoxy reactive diluent, the catalyst in 8 uses nano-γ-Al2O3 (purity ≥ 99.5%, D 90 =10~20nm), select the raw materials listed in 3-7; the synthesized product retains the reactive epoxy group, and the product is called epoxy nano-organic titanium polymer, abbreviated as TPP-1. Its mechanochemical reaction process can be expressed by the following structural formula:

[0029]

[0030] Preferably, in 1-8, when 1-2 uses a liquid low-viscosity epoxy resin and an epoxy active diluent, the catalyst in 8 uses sodium hydrogen phthalate (C8H7NaO4), and 3-7 each uses the listed raw materials; in the synthesis, titanium hydride combines with the open-ring oxygen acceptor during the nano-process to form a hydroxyl group, and the product is called a hydroxyl nano-organic titanium polymer, abbreviated as TPP-2. Its mechanochemical reaction process can be expressed by the following structural formula:

[0031]

[0032] Preferably, in 1-8, when phenoxy resin and phenoxy active diluent are selected in 1-2, the raw materials listed in 3-7 are selected, and the catalyst in 8 is not selected; in the synthesis, the phenoxy resin is directly blended and copolymerized with titanium hydride, and the obtained product is also hydroxy nano-organic titanium polymer TPP-2. Its mechanochemical reaction process can be represented by the following structural formula:

[0033]

[0034] The nano-organic titanium polymers generated above are divided into epoxy nano-organic titanium polymer TPP-1 and hydroxy nano-organic titanium polymer TPP-2. Although the raw material combination methods are slightly different, the products are both nano-organic titanium polymers with the same main characteristics: both have the anti-corrosion and corrosion-resistant properties of titanium, and are also used as film-forming matrices in industrial heavy-duty anti-corrosion coatings. The only difference is the auxiliary ingredients added when making the coatings. TPP-1 uses an organic amine prepolymer as a curing agent, and TPP-2 uses an isocyanate prepolymer as a curing agent. The former is not weather-resistant and cannot be used for outdoor coatings (it will powderize); the latter is weather-resistant and can be used both indoors and outdoors.

[0035] 2. Process for preparing nano-organic titanium polymer

[0036] The present invention adopts a planetary ball mill (high energy ball mill) reactor to synthesize and prepare the nano-organic titanium precursor. The specific preparation steps are as follows:

[0037] Step 1: Add four kinds of graded grinding balls (zirconium balls or stainless steel balls) into a planetary ball mill reactor, which are Φ20 mm, Φ15 mm, Φ10 mm, and Φ5 mm, respectively, and the mass ratio is 10-20:15-25:20-30:25-40;

[0038] Step 2: Weigh the raw material components according to the mass fractions of the raw materials and the proportions in "a": 50-200 parts of liquid low-viscosity epoxy resin or phenoxy resin, 200-400 parts of epoxy reactive diluent or phenoxy reactive diluent, 500-800 parts of titanium hydride fine powder, 50-150 parts of nano material dispersant, 20-50 parts of polymer toughening agent, 5-20 parts of coupling agent, 1-10 parts of functional additive, 0-10 parts of γ-phase nano alumina (γ-Al2O3) or sodium hydrogen phthalate (C8H7NaO4) catalyst, then mix and disperse the materials evenly, and put them into a planetary ball mill reactor;

[0039] Step 3: Start the planetary ball mill reactor. At the beginning, stop the reactor every 1 hour, open the top of the reactor to vent once, then close it and run it again. Run it for 3 hours and vent it three times. Then, run it continuously for 3 to 7 hours. When the cumulative running time is ≧6 hours, the material has reacted, the temperature in the reactor reaches about 160°C, and the pressure reaches about 0.6MPa. After the reaction is completed, because the reactor is in a sealed state, the pressure and temperature will still increase, and the pressure can reach about 0.8MPa and the temperature can reach about 180°C. Therefore, when the cumulative time is 6 to 10 hours, the temperature in the reactor is measured to reach 160 to 180°C and the pressure reaches 0.6 to 0.8MPa, stop the reactor.

[0040] Step 4: Cooling and depressurizing. After the reactor is naturally cooled to room temperature, a pump is inserted into the bottom of the reactor to extract all the materials to obtain a black sludge-like product, which is the nano-organic titanium polymer.

[0041] Preferably, in steps 1 and 2, the ratio of the total mass of the raw materials to the total mass of the grinding balls is 1:2-5, preferably 1:2;

[0042] Preferably, in step 2, the titanium fine powder raw material titanium hydride fine powder is added in excess during the formulation design. This is because in the nano-process, not all nano-titanium can participate in the graft polymerization reaction because there is no reaction site. Therefore, the remaining nano-titanium particles that fail to participate in the reaction are wrapped by the dispersant and doped in the polymer system, which can play a hybrid effect. This hybrid effect is integrated in the nano-organic titanium polymer, which is very beneficial to the enhancement of its anti-corrosion performance;

[0043] Preferably, in step 3, when the ball milling time is ≥ 6 hours, the reaction temperature in the reactor is 160°C, and the pressure is 0.6 MPa, the particle size distribution of the nano-organic titanium polymer is in the optimal range D 90 =10~100nm.

[0044] 3. Process for preparing titanium-based polymer alloy copolymer

[0045] 1. Raw material composition

[0046] (1) 600 parts of nano-organic titanium polymer;

[0047] (2) 400 parts of 40% polymer resin liquid;

[0048] (3) 0 to 5 parts of Ziegler-Natta catalyst.

[0049] Preferably, the nano-organic titanium polymer in (1) is an epoxy nano-organic titanium polymer TPP-1 or a hydroxy nano-organic titanium polymer TPP-2, preferably TPP-2;

[0050] Preferably, the 40% polymer resin liquid in (2) is 40% poly(phenylene ether sulfone ketone) (PPESK) or 40% poly(phenylene ether nitrile ketone) (PPENK) or 40% soluble polyamideimide (PAI).

[0051] 2. Preparation of 40% polymer resin liquid: Take the following raw materials: 100 parts of N-methylpyrrolidone (NMP), 150 parts of N,N-dimethylacetamide (DMA), 350 parts of N,N-dimethylformamide (DMF), 400 parts of poly(phenylene ether sulfone ketone) (PPESK) or poly(phenylene ether nitrile ketone) (PPENK) or soluble polyamideimide (PAI), put them into a dissolving kettle and heat-dissolve them at 80°C until they are clear and transparent with no undissolved matter. After they are completely dissolved, 40% PPESK resin liquid or 40% PPENK resin liquid or 40% PAI resin liquid is obtained.

[0052] 3. Preparation method

[0053] (1) Blend and disperse the raw materials (1), (2), and (3) in step (1) uniformly;

[0054] (2) injecting the above-mentioned uniformly blended raw materials into a planetary ball mill reactor;

[0055] (3) Add four kinds of graded grinding balls (zirconium balls or stainless steel balls) into the planetary ball mill reactor, namely Φ20 mm, Φ15 mm, Φ10 mm, and Φ5 mm, with a mass ratio of 10-20:15-25:20-30:25-40; start the ball mill reactor and run it continuously for 3-6 hours;

[0056] (4) When the running time is ≥ 3 hours and the temperature in the kettle reaches about 120°C, the materials begin to react, and the reaction process also releases heat, so the temperature in the kettle can reach 160°C; when the temperature in the kettle reaches 120-160°C, the machine is shut down;

[0057] (5) Keep the temperature for 1 hour, and then discharge the material to obtain titanium-based poly(arylethersulfoneketone) copolymer (abbreviated as TPESK) or titanium-based poly(arylethernitrileketone) copolymer (abbreviated as TPENK) or titanium-based polyamideimide copolymer (abbreviated as TPAI).

[0058] Preferably, when the ball mill reactor in (3) is in operation, ultrasonic wave-assisted synthesis is used without adding Ziegler-Natta catalyst, and the operation is continued for 3 hours;

[0059] Preferably, the mass ratio of balls to materials in (2) and (3) is 2:1.

[0060] The reaction equation for generating titanium-based polyarylethersulfoneketone copolymer is as follows:

[0061] The reaction equation for generating titanium-based polyarylether nitrile ketone copolymer is as follows:

[0062]

[0063]

[0064] The reaction equation for ultrasonic-assisted generation of titanium-based polyamide-imide copolymer is as follows:

[0065]

[0066] 4. Preparation method of coating

[0067] 1. Solvent-free nano-organic titanium heavy-duty anti-corrosion coating prepared with nano-organic titanium polymer as the matrix film-forming material

[0068] (1) Raw materials

[0069] The raw material uses nano-organic titanium polymer as the matrix film-forming material, and the composition also includes auxiliary film-forming materials, active diluents, pigments and fillers, coating additives, curing agents and other materials.

[0070] The nano-organic titanium polymer includes epoxy nano-organic titanium polymer TPP-1 or hydroxy nano-organic titanium polymer TPP-2;

[0071] The auxiliary film-forming material includes phenoxy resin, epoxy resin, phenolic resin, polyurethane resin, etc., but is not limited thereto;

[0072] The reactive diluent (reactive solvent) mentioned herein includes epoxy reactive diluent (such as multifunctional glycidyl ether or ester), polyurethane reactive diluent (such as bis-oxazolidine), etc., but is not limited thereto;

[0073] The color fillers include coloring pigments, anti-rust pigments and body pigments. The coloring pigments include inorganic carbon black, iron black, iron red, iron yellow, chrome yellow, zinc chrome yellow, chrome green, cobalt blue, titanium white, etc., and organic phthalocyanine series, aniline series, azo series, anthraquinone series and ketone series and other color pigments; the anti-rust pigments include metal anti-rust pigments (such as zinc powder, aluminum powder, etc.) and inorganic phosphates, chromates, titanates (containing zinc, aluminum, calcium, iron, titanium salts, etc.); the body pigments include metal oxides and inorganic salts, such as talc, mica powder, silica fume, zinc oxide, calcium carbonate, barium sulfate, etc., but not limited to these;

[0074] The coating additives mentioned include wetting agents, dispersants, defoamers, leveling agents, thickeners, thixotropic agents and other functional additives, but are not limited thereto;

[0075] The curing agent mentioned herein includes polyamine and modified amine epoxy curing agents, aliphatic polyisocyanate curing agents and other types of curing agents.

[0076] (2) Proportion

[0077] a: The two-component coating is composed of component A and component B, with TPP-1 as the film-forming material. The basic raw material combination and formula and its manufacturing method are as follows:

[0078] ① Raw material composition of component A (by mass): 5-20 parts of TPP-1, 25-30 parts of liquid epoxy resin, 5-10 parts of epoxy reactive diluent, 20-30 parts of anti-rust pigment, 10-20 parts of body pigment, 0.5-1.0 parts of dispersant, 0.5-1.5 parts of anti-settling agent, 0.5-2.0 parts of thickener, 0.1-1.0 parts of defoaming agent, 0.1-1.0 parts of leveling agent, 0.5-2.5 parts of coupling agent, 3-10 parts of toughening agent, 0.5-2 parts of thixotropic agent.

[0079] ② Component B is a solvent-free polyamine epoxy curing agent: amine value: 200-600 mg KOH / g; viscosity ≤5000 mPa·s.

[0080] The mass ratio of group A to group B is 1 to 10:1; the preferred mass ratio is 4 to 10:1.

[0081] b: The two-component coating is composed of component A and component B, with TPP-2 as the film-forming material. The basic raw material combination and formula and its manufacturing method are as follows:

[0082] ① Raw material composition of component A (by mass): 5-20 parts of TPP-2, 25-30 parts of solvent-free polyaspartic acid ester resin (or solvent-free polyurethane resin), 5-10 parts of oxazolidine active diluent, 20-30 parts of anti-rust pigment, 10-20 parts of body pigment, 0.5-1.0 parts of dispersant, 0.5-1.5 parts of anti-settling agent, 0.5-2.0 parts of thickener, 0.1-1.0 parts of defoaming agent, 0.1-1.0 parts of leveling agent, 0.5-2.5 parts of coupling agent, 3-10 parts of toughening agent, 0.5-2 parts of thixotropic agent.

[0083] ② Component B is a solvent-free HDI trimer curing agent: NCO content requirement: 21% to 23%; viscosity 1700 to 4000 mPa·s.

[0084] The mass ratio of group A to group B is 1-10:1; the preferred mass ratio is 4-5:1.

[0085] c: Coating process and manufacturing technology are carried out in the following steps:

[0086] ① Preparation of component A: weigh the raw materials according to the ratio and mass parts, use a high-speed disperser to shear and disperse for 20 to 30 minutes, then grind in a basket sand mill equipped with zirconium balls to a particle size of ≤20μm, and pack;

[0087] ② Preparation of component B: Mix and disperse the curing agent evenly and package it.

[0088] ③ When using, mix group A and group B in a mass ratio of 4 to 5:1.

[0089] 2. Special coatings prepared with titanium-based polymer alloy copolymer as the main film-forming material

[0090] (1) Raw materials

[0091] The raw material selected is titanium-based polymer alloy copolymer as the main film-forming material, and its composition also includes auxiliary film-forming resin, color filler, coating additive, polar solvent and curing agent and other materials.

[0092] The titanium-based polymer alloy copolymers include titanium-based polyarylether nitrile ketone (TPENK), titanium-based polyarylether sulfone ketone (TPESK) and titanium-based polyamide-imide (TPAI) copolymers;

[0093] The auxiliary film-forming resins include phenoxy resins, epoxy resins, phenolic resins, polyurethane resins, etc., but are not limited thereto;

[0094] The color fillers include coloring pigments, anti-rust pigments and body pigments. The coloring pigments include inorganic carbon black, iron black, iron red, iron yellow, chrome yellow, zinc chrome yellow, chrome green, cobalt blue, titanium white, etc., and organic phthalocyanine series, aniline series, azo series, anthraquinone series and ketone series and other color pigments; the anti-rust pigments include metal anti-rust pigments (such as zinc powder, aluminum powder, etc.) and inorganic phosphates, chromates, titanates (containing zinc, aluminum, calcium, iron, titanium salts, etc.); the body pigments include metal oxides and inorganic salts, such as talc, mica powder, silica fume, zinc oxide, calcium carbonate, barium sulfate, etc., but not limited to these;

[0095] The coating additives mentioned include wetting agents, dispersants, defoamers, leveling agents, thickeners, thixotropic agents and other functional additives, but are not limited thereto;

[0096] The polar solvents described therein are limited to chloroform, dimethylformamide, dimethylacetamide and N-methylpyrrolidone;

[0097] The curing agent mentioned herein includes room temperature curing agent, high temperature latent curing agent and latent curing agent. The so-called room temperature curing agent includes polyamine and modified amine epoxy curing agent, aliphatic polyisocyanate curing agent, solvent-free HDI trimer curing agent and other types of curing agents; the so-called high temperature curing agent includes epoxy resin high temperature resistant curing agent and epoxy resin high temperature curing agent; the so-called latent curing agent includes dicyandiamide and its modified amine, dapsone, imidazole, acid anhydride, blocked isocyanate curing agent, etc.

[0098] (2) Types

[0099] The coating is a series of products, including special and general products. According to the application and film-forming mechanism, it is divided into single-component and two-component coating products. The proportion is determined according to the actual needs of special and general use, as shown in the embodiments.

[0100] The special products mentioned above are single-component coatings, and the raw materials include: titanium-based polymer alloy copolymer as the main film-forming material, auxiliary film-forming resin, pigments and fillers, coating additives, polar solvents and latent curing agents. They are mainly used in single-component coatings for on-site construction in factory workshops or with special facilities such as cranes, sandblasting rooms, paint spraying rooms, paint dipping tanks, drying rooms, etc.

[0101] The special products mentioned include special coatings for large industrial heat exchangers, special coatings for drag reduction in oil and gas field well pipes and long-distance pipelines, special coatings for color-coated steel sheets for home appliances, home furnishings and furniture, etc.

[0102] The general-purpose product is a two-component coating, and the raw material composition A component includes: titanium-based polymer alloy copolymer as the main film-forming material, auxiliary film-forming resin, pigment filler, coating additive, polar solvent and other materials; component B includes: room temperature curing agent or high temperature latent curing agent. It is mainly used for the two-component coating varieties that cure at room temperature in the on-site construction of large structures;

[0103] The general-purpose products mentioned include heavy-duty anti-corrosion coatings for onshore and offshore steel structures, and heavy-duty anti-corrosion coatings used in harsh working conditions and high-temperature environments;

[0104] The method for preparing a coating from a titanium-based polymer alloy copolymer is characterized in that it comprises the following steps:

[0105] Special one-component coating: Step 1, take the raw material titanium-based polymer alloy copolymer as the main film-forming material, and mix the auxiliary film-forming resin, pigment filler, coating additive, polar solvent and latent curing agent; Step 2, use a high-speed disperser to shear and disperse for 20 to 30 minutes, and then place it in a basket sand mill equipped with grinding balls to grind to a particle size of ≤20μm; Step 3, discharge the material and bag it.

[0106] Universal two-component coating: Step 1, Component A: Titanium-based polymer alloy copolymer as the main film-forming material, auxiliary film-forming resin, pigment filler, coating additive, polar solvent are mixed, sheared and dispersed using a high-speed disperser for 20 to 30 minutes, then placed in a basket sand mill equipped with grinding balls and ground to a particle size of ≤20μm, and packaged; Step 2, Component B: Mix and disperse the normal and high temperature curing agents evenly, and package. Step 3, when using, mix Group A and Group B evenly at a mass ratio of 4 to 5:1.

[0107] V. Beneficial Effects of the Invention

[0108] The technical solution of the present invention is designed and implemented according to the principle of mechanochemistry. In the mechanochemical reaction, the polymer, under the action of mechanical force, generates critical stress to break the chemical bonds due to uneven distribution of internal stress or impact energy concentrated on individual segments. The most important feature when the chemical bonds are broken is the generation of chemical active centers (free radicals). The position of chemical bond breaking (force degradation) depends on the stress concentration on the individual segments of the polymer, the nodes of the branched polymer with the main chain, the horizontal bonds in the network, the main chain containing heteroatoms, and a certain node where the stress is concentrated when the polymer is deformed. The present invention prepares nano-organic titanium polymers by utilizing the heteroatoms (ROC) on the main chain of the epoxy resin structure, breaking the chains and bonds through the action of mechanochemistry, and molecular rearrangement occurs by graft bonding with titanium atoms to generate metal titanium organic polymers with a completely new molecular structure.

[0109] This reaction is divided into two processes: the first stage is the process in which the atoms of the titanium hydride powder at the interface of the nanoparticles absorb energy and release H2 during the nano-process; at the same time, the epoxy resin breaks chains and bonds under the action of mechanical shear and friction. According to mechanochemistry theory, bond breaking first occurs on the OC bond containing heteroatoms (i.e., COC) in the main chain; the second stage is the energy conversion process of nano-titanium, that is, the process in which missing bonds (oxygen-deficient bonds) appear on the surface of titanium atoms to compete for oxygen atoms in the epoxy resin. At this time, the C atoms with broken chains on the main chain of the epoxy resin compete with the Ti atoms with broken bonds for O atoms. Since the Ti-O bond energy is 662kJ / mol and the CO bond energy is 326kJ / mol, Ti-O>CO, and finally the broken chain O atoms are captured by the broken bond Ti atoms to undergo graft bonding. The chemical formula of the reaction process is shown in the figure. Figure 2 shown.

[0110] From the test results after the experiment, Figure 5 The infrared spectrum of epoxy resin E-51 before the experiment is the upper spectrum peak, the original titanium powder before the experiment is the middle spectrum peak, and the infrared spectrum of the original titanium powder before ball milling is only at 3425cm -1 and 1639 -1 There are two obvious characteristic absorption peaks at 2800-3000cm, which are the characteristic absorption peak of OH stretching vibration and the characteristic absorption peak of OH stretching vibration of adsorbed water. The material after titanium powder is blended and ground with epoxy resin is the lower peak of the spectrum, and its intensity is significantly different from that of E-51 epoxy resin. -1 and 700~1600cm -1 The characteristic absorption peak appeared in the band, but the position of the characteristic absorption peak was basically the same as the upper spectrum peak before the E-51 experiment, indicating that after the titanium powder and epoxy resin were blended and ball-milled, the product structure changed, and the organic combination of titanium powder and epoxy resin was achieved.

[0111] Figure 6 This is the FT-IR spectrum of TiH2 / NPEL-128 (same as E-51) epoxy resin blended before ball milling. -1 There are three weak absorption bands in the frequency band, which are caused by the free OH(ν O-H ) stretching vibration characteristic absorption peak, which is consistent with Figure 5 It is consistent with the intermediate spectrum (original titanium powder).

[0112] Figure 7 This is the FT-IR spectrum of TiH2 / NPEL-128 blended after high-energy ball milling for 3 hours. It can be seen from the figure that in the range of 3500-1700 cm -1In the frequency band, only a weak phenyl stretching vibration peak appears, and no new characteristic peaks appear, indicating that the grain size of titanium hydride powder becomes smaller, the lattice distortion increases, and the blended material is still in the nano-process stage, so no obvious chemical changes occur, only a material refinement process.

[0113] Figure 8 This is the FT-IR spectrum after ordinary ball milling for 30 hours. Figure 7 Compared with the spectrum after ball milling for 3 hours, Figure 7 2800cm -1 The OH stretching vibration peak at is still relatively weak. Figure 8 The OH stretching vibration peak in the -1 position, and weakened; and at 3200cm~2700cm -1 The frequency band shows the characteristic peak of epoxybenzene ring; 1700cm -1 Up to 600cm -1 Frequency band, basic and Fig. 9 Similar. This is because when the grinding time and the change of titanium powder particles reach a dynamic equilibrium state, and the dispersion speed of titanium nanoparticles is less than their agglomeration speed, the agglomeration degree of titanium nanoparticles will increase, affecting their mechanochemical reaction efficiency, and will also affect the properties of the product. Therefore, it can be considered that the grinding time should be neither too short nor too long. There is a balance between the ball milling time and the particle size of titanium powder. After 3 hours of grinding, it is obvious that the material has not yet undergone "chain breaking and grafting"; after 30 hours of grinding, the material has completed "chain breaking and grafting". The delayed time not only does not improve the quality of the material, but affects the efficiency of material production.

[0114] Fig. 9 This is the FT-IR characteristic spectrum of the titanium base material after high-energy ball milling for 6 hours. -1 There are three sharp stretching vibration areas in the frequency band, which are epoxybenzene rings; at 2400~2100cm -1 The spectral band in the band is weak CH, from 1700cm -1 Up to 500cm -1 The spectral peaks in the frequency band are relatively concentrated; at 1670~1500cm -1 The first long and sharp peak appears at 1300-1000cm -1 It is also the stretching vibration peak of CO; at 1300~800cm -1 Frequency band, -CH3 and phenyl stretching vibration peak; 850~700cm -1 The epoxy group of hydrocarbon is bent (б O-C ) vibration peak; 700cm -1 Up to 600cm -1The section is the vibration peak of Ti-O bond and CH bond. It can be seen that the quality and efficiency of the produced materials are better during this period.

[0115] Fig.10 The XRD spectrum of the titanium base material after 6 hours of high-energy ball milling of TiH2 / EP128 further verifies the effect of the present invention. From the XRD spectrum analysis results, the upper spectrum ◆- is the Ti phase spectrum of TiH2 powder without grinding, and the lower spectrum is the Ti phase and ● -Fe phase composition. Compared with the upper spectrum, the ◆-Ti phase peak in the lower spectrum is significantly weaker and broader than the ◆-Ti phase diffraction peak in the upper spectrum, indicating that the Ti powder content is reduced and the crystal phase tends to be amorphous and disordered (the ● -Fe phase is the metallographic impurities that are worn away by friction between balls and between balls and tank walls during the grinding process.

[0116] Fig.11 FT-IR spectra of hydroxy nano-titanium polymer (TPP-2) and poly(phenylene ether sulfone ketone) (PPESK) before ball milling;

[0117] Fig.12 and Fig.13 All are FT-IR spectra of titanium-based poly(aryl ether sulfone ketone) copolymer (TPESK) after ball milling.

[0118] Fig.12 This is the FT-IR spectrum of TPP-2 / PPESK blend after high-energy ball milling for 6 hours. Fig.11 The characteristic peaks in the original -1 、2930~2872cm -1 、2359~1670cm -1 The wavelength band is obviously weakened or disappeared, and four new characteristic peaks appear, namely 1550cm -1 、1300cm -1 , 1000cm -1 and 750cm -1 ,and Fig.11 Compared with the above, the spectrum has changed greatly, indicating that the material has undergone a copolymerization chemical reaction and formed a new structural spectrum. Therefore, it can be determined that Fig.12 It is the characteristic infrared spectrum of the polymer alloy copolymer - titanium-based polyarylethersulfoneketone copolymer (TPESK).

[0119] Fig.13 This is the FT-IR spectrum of TPP-2 / PPESK blend after ultrasonic assisted ball milling for 3 hours. Fig.13 and Fig.12 In comparison, at 3000-1670cm -1The segment has obvious similarities, which is the characteristic peak of poly(arylethersulfoneketone), but at 3800-3400cm -1 There is an obvious forward shift in the section. Fig.12 3300cm -1 The vibration peak is Fig.13 It weakened and disappeared at 3500cm -1 A strong absorption peak appeared at 1500-500 cm -1 The characteristic peaks of the frequency band are significantly weakened and narrowed; in the range of 1700-1200cm -1 In the frequency band, the absorption vibration peak is relatively chaotic, which is caused by the interference of the additive, but in Fig.13 The phase becomes clear. This is because in the ultrasonic assisted ball milling process, the materials do not need to add grinding aids, and the same new polymer products can be obtained. It also verifies that ultrasonic assisted ball milling plays a positive role in promoting the mechanochemical synthesis of organic polymers, which can greatly shorten the polymerization reaction time and improve the ball milling reaction efficiency.

[0120] The above experiments and test results show that the present invention has the following beneficial effects:

[0121] 1. The present invention has conducted long-term and in-depth exploration and practice in scientifically and rationally adjusting the raw material formula, improving the process flow, and standardizing the preparation method. In particular, the present invention has explored a set of scientific and reasonable procedures and configuration parameters in the selection of main synthetic materials such as titanium materials and resins, the use of catalysts, the types and proportions of auxiliary raw materials, the control of temperature, pressure, and time during the reaction process, as well as the improvement and adjustment of production equipment, which directly determine the degree of completion of "chain breaking, bond breaking, grafting polymerization" and the quality of nano-titanium organic polymers. The present invention overcomes the defects in the prior art and solves the problems of high quality and stability of nano-organic titanium polymers and titanium-based polymer alloy copolymers. The nano-organic titanium polymers prepared by the method of the present invention are observed under a scanning electron microscope. Most of the particle size distribution is in the range of D90=10 to 100 nm. Figure 3 As shown; through the laser particle size analyzer detection and analysis, the D90 particle size distribution of 30-60nm is greater than 50%, see Figure 4 As shown; after being stored at room temperature for 90 days, the system is stable without agglomeration, sedimentation or stratification. These all indicate that the quality index of the nano-organic titanium polymer produced by the present invention fully meets the requirements, and the actual application effect of the coating prepared with it as the film-forming matrix reaches the existing industrial anti-corrosion standard, which is further explained in the embodiments.

[0122] 2. Innovative methods. Mechanochemistry is a complex physical and chemical process that has greatly surpassed the scope of traditional thermochemical thinking. When polymers are subjected to mechanochemical action, chemical changes such as force cracking, structuring, cyclization, ionization and isomerization will occur. Therefore, mechanochemistry can be used to induce chemical reactions that are difficult or impossible to carry out by thermochemistry, and can be used to prepare some high-performance structural materials or synthesize new polymer alloy functional materials. Therefore, the present invention has created a new way of thinking, new ideas, new methods and new experiences for scientific and technological innovation and research and development of new materials.

[0123] 3. Energy saving and environmental protection. The coatings made of the new materials of the present invention continuously present new functions during performance testing and practical application. So far, "nine major functions" have been discovered and summarized: high temperature resistance, high pressure resistance, corrosion resistance, aging resistance, static electricity conduction, anti-fouling (non-stickiness), anti-scaling and drag reduction, shielding of electromagnetic radiation, and prevention of marine biological attachment. The application of these coatings replaces expensive special steel materials, prolongs the service life of petrochemical engineering materials and marine engineering materials, and significantly reduces costs and saves materials. The preparation process uses environmentally friendly and pollution-free raw materials, which plays a positive role in environmental protection.

[0124] 4. Complete import substitution. The successful development of nano-organic titanium polymers and titanium-based polymer alloy copolymers has provided high-performance new film-forming matrix materials for the fine chemical industry (special coatings, special inks, special adhesives), and has also expanded the field of industrial heavy-duty anti-corrosion application technology. The special coatings made from them have filled the gap in domestic high-performance products and solved key technologies in many applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0125] Figure 1 Schematic diagram of planetary ball mill reactor;

[0126] Figure 2 Mechanochemical reaction process of nano-organic titanium polymer;

[0127] Figure 3 Electron microscopy characterization of nano-organic titanium polymer after ball milling;

[0128] Figure 4 Electron microscopic characterization of nano-organic titanium polymer during ball milling;

[0129] Figure 5 FT-IR spectra of Ti / E51 resin and titanium before and after ball milling;

[0130] Figure 6 FT-IR spectrum of TiH2 / EP128 resin before ball milling;

[0131] Figure 7 FT-IR spectrum of TiH2 / EP128 with ordinary ball milling for 30 hours;

[0132] Figure 8 FT-IR spectrum of TiH2 / EP128 after high-energy ball milling for 3 hours;

[0133] Fig. 9 FT-IR spectrum of TiH2 / EP128 after high-energy ball milling for 6 hours;

[0134] Fig.10 XRD spectra of TiH2 / EP128 polymer before and after high-energy ball milling;

[0135] Fig.11 FT-IR spectrum of TPP-2 / PPESK blends before ball milling;

[0136] Fig.12 FT-IR characteristic spectrum of TPP-2 / PPESK after high-energy ball milling for 6 hours;

[0137] Fig.13 FT-IR characteristic spectrum of TPP-2 / PPESK after ultrasonic high-energy ball milling for 3 hours.

[0138] Figure numerals: 1 - planetary ball mill reactor; 2 - switch; 3 - reactor top cover. VII. Implementation Examples

[0139] (I) Main equipment and main raw materials

[0140] 1. Main equipment

[0141] ① Planetary high energy ball mill reactor, such as Figure 1 ;

[0142] ②Vertical disperser; basket sand mill.

[0143] 2. Main raw materials

[0144] ① Basic material: titanium hydride fine powder (TiH2), specification: Φ1~10μm, purity: Ti≥99.5%;

[0145] ② Liquid low-viscosity epoxy resin, such as EP128 epoxy resin, with no obvious mechanical impurities on the surface; epoxy value: 0.48-0.54eq / 100g; viscosity (25°C): ≤2500mPa·s; organic volatile matter: ≤1%; it can also be EP127, GT-807, DEN-431, etc. (not limited to these);

[0146] ③ Epoxy reactive diluent: multifunctional glycidyl ether or multifunctional glycidyl ester, commercially available; relative density: 1.172; epoxy value: 0.50-0.60eq / 100g; viscosity (25°C): ≤85mPa·s; organic volatile matter: ≤1.0% (not limited to this);

[0147] ④ Toughening agent: CTPB-II carboxyl-terminated liquid polybutadiene rubber, JLY-124 liquid polysulfide rubber, NBR-1704 liquid nitrile rubber, etc. (not limited to these);

[0148] ⑤ Catalyst: γ-phase nano-alumina (Al2O3): Φ10~20nm, purity ≥99.5% (not limited to this);

[0149] ⑥Nanomaterial dispersants: TAZ-ND1, AKN-2300, PDT-IC1, KYC-913, etc. (not limited to these);

[0150] ⑦ Coupling agent: coupling agent ZJ-401, coupling agent KH-550, etc. (not limited to these);

[0151] ⑧ Functional additives: BYK-defoaming agent and leveling agent, organic bentonite F-881B, F-118 anti-settling agent, aluminum zinc phosphate, mica iron oxide red, zinc chrome yellow, mica powder, zinc powder, aluminum powder and other anti-rust pigments and body pigments, etc. (not limited to these).

[0152] Note: The capital letters and numbers before and after the names of the raw materials are the product models of different manufacturers and brands of products, such as: EP128 epoxy resin (a liquid epoxy resin synthesized from bisphenol A and epichlorohydrin, with excellent mechanical strength, chemical resistance and heat resistance), organic bentonite F-881B (an organic clay series product, mainly used as a thickener, viscosity regulator, anti-settling agent, thixotropic agent and latex stabilizer), etc.; the names of the raw materials and equipment listed are also the names commonly used in the industry.

[0153] (II) Synthesis of Nano-organic Titanium Polymers by Mechanochemical Method

[0154] Example 1

[0155] The raw material composition of the nano-organic titanium polymer (by mass): 200 parts of EP128 epoxy resin, 400 parts of 1,2-cyclohexanediol diglycidyl ether, 500 parts of titanium hydride fine powder (Φ1~5μm), 10 parts of γ-phase nano-alumina (Al2O3), 100 parts of TAZ-ND1 nano-dispersant, 50 parts of terminal hydroxyl liquid polybutadiene rubber, 20 parts of KH-550 silane coupling agent, and 10 parts of F-118 anti-settling agent.

[0156] The preparation method of the above-mentioned nano-organic titanium polymer comprises the following steps:

[0157] (1) Four grinding balls with different particle size distributions (which can be zirconium balls or 316L stainless steel balls) are weighed by weight and placed in a 1-planetary ball mill reactor. The particle sizes of the grinding balls are Φ20 mm, Φ15 mm, Φ10 mm, and Φ5 mm, respectively, and the mass ratio is 10:20:30:40;

[0158] (2) Weigh each raw material component by weight and place it in a container. After the materials are mixed and dispersed evenly, open the inlet and outlet valves of the planetary ball mill reactor top cover 3, inject the materials into the reactor through a pneumatic diaphragm pump, close the reactor top cover 3, the mass ratio of the balls to the materials in the tank is 2:1, and the reactor top cover 3 is tightened and sealed with bolts;

[0159] (3) Start the planetary ball mill reactor power switch 2 and operate it. For the first three hours, stop the reactor every one hour, open the reactor top cover 3 to vent and then close it, and do this three times. Then continue to operate for three hours. When the temperature in the reactor reaches 160° C. and the pressure reaches 0.6 MPa, stop the reactor, cool it down, release the pressure, and discharge the materials (insert the steel pipe at the suction end of the pump into the bottom of the reactor to extract all the materials), and obtain a black viscous product, epoxy nano-organic titanium polymer TPP-1.

[0160] During the ball milling process, TiH2 will continuously release H2 due to the nano-process, which will cause the lattice of nanoparticles to be disordered and the chemical bonds to be broken. The gas will expand in volume due to the heat of grinding, causing overpressure in the reactor. Therefore, it is necessary to shut down and exhaust the gas after running for a period of time, otherwise an explosion will occur.

[0161] Example 2

[0162] The material composition of the nano-organic titanium polymer (by mass): 350 parts of EPM-304H multifunctional triglycidyl p-aminophenol (viscosity 500-800 mPa·s), 200 parts of DEN-431 phenolic epoxy resin (produced in the United States), 800 parts of titanium hydride fine powder (Φ1-5μm), 10 parts of γ-phase nano-alumina (Al2O3), 50 parts of JLY-124 liquid polysulfide rubber, 100 parts of AKN-2300 nano-dispersant, 20 parts of KH-570 silane coupling agent, 5 parts of functional additive F118 anti-settling agent and 5 parts of SD-1 organic bentonite.

[0163] The preparation method of the above-mentioned nano-organic titanium polymer comprises the following steps:

[0164] (1) Four grinding balls with different particle size distributions (which can be zirconium balls or 316L stainless steel balls) are weighed by weight and placed in a 1-planetary ball mill reactor. The particle sizes of the grinding balls are Φ20 mm, Φ15 mm, Φ10 mm, and Φ5 mm, respectively, and the mass ratio is 10:20:30:40;

[0165] (2) Weigh each raw material component by weight and place it in a container. After the materials are evenly mixed and dispersed, open the inlet and outlet valves of the planetary ball mill reactor top cover 3, inject the materials into the reactor through a pneumatic diaphragm pump, close the reactor top cover 3, the mass ratio of the balls to the materials in the tank is 5:1, and the reactor top cover is tightened and sealed with bolts;

[0166] (3) Start the planetary ball mill reactor power switch 2 and operate it. For the first 3 hours, stop the reactor every 1 hour, open the reactor top cover 3 to vent and then close it, and do this three times. Then continue to operate for 7 hours. When the temperature in the reactor reaches 180° C. and the pressure reaches 0.8 MPa, stop the reactor, cool it down, release the pressure, and discharge the materials (insert the steel pipe at the suction end of the pump into the bottom of the reactor to extract all the materials), and obtain a black viscous product, epoxy nano-organic titanium polymer TPP-1.

[0167] Example 3

[0168] The material composition of the nano-organic titanium polymer (by mass): 350 parts of 692 epoxy reactive diluent, 200 parts of GT-807 low-viscosity epoxy resin, 600 parts of titanium hydride fine powder (Φ1-5μm), 10 parts of γ-phase nano-alumina (Al2O3), 20 parts of NBR-1704 liquid nitrile rubber, 20 parts of ZJ-401 titanate coupling agent, 100 parts of KYC-913 nano-dispersant, and 10 parts of D670 liquid elastic saturated polyester resin.

[0169] The preparation process and method are the same as those of Example 1 (1), (2), and (3).

[0170] In Examples 1 to 3, although different epoxy resins were used, the synthesized products were the same, that is, the reactive epoxy groups were retained, and the product was an epoxy-based organic titanium polymer TPP-1. The reaction process is as follows:

[0171]

[0172] Example 4

[0173] Material composition of nano-organic titanium polymer (by mass): 400 parts of DY-31 trimethylolethane triglycidyl ether, 200 parts of EP127 epoxy resin, 700 parts of titanium hydride powder (Φ1~5μm), 100 parts of KYC-913 nano-dispersant, 20 parts of sodium hydrogen phthalate (C8H7NaO4) catalyst, 20 parts of terminal hydroxyl liquid polybutadiene rubber, 10 parts of KH-560 silane coupling agent, and 10 parts of F118 anti-settling agent.

[0174] The preparation process and method are the same as those of Example 2 (1), (2), and (3).

[0175] In the present embodiment, sodium hydrogen phthalate (C8H7NaO4) is added as a catalyst instead of γ-phase nano-alumina (Al2O3), and reacts with epoxy groups according to the nucleophilic mechanism. In the presence of a strong organic acid salt catalyst, the epoxy groups undergo a ring-opening reaction at a high temperature of about 150°C. Titanium hydride will release a large amount of active hydrogen due to the rupture of lattice bonds during the nano-processing process, and combine with the ring-opened oxygen acceptor to form a hydroxyl functional group, so that the conversion process can be completed, and the obtained product is a hydroxyl-containing nano-organic titanium polymer TPP-2. Its reaction process is as follows:

[0176]

[0177] Example 5

[0178] The material composition of the nano-organic titanium polymer (by mass): 200 parts of dimethyl sulfoxide (DMSO), 200 parts of ALT-202 bisoxazolidine active diluent, 150 parts of YP-50S phenoxy resin, 100 parts of KYC-913 nano-dispersant, 700 parts of titanium hydride fine powder (Φ1-5μm), 20 parts of NBR-1704 liquid nitrile rubber, 20 parts of KH-550 silane coupling agent, and 10 parts of D670 liquid elastomer saturated polyester resin.

[0179] First, use DMSO + ALT202 solvent to heat dissolve YP-50S solid resin, and repeat the other process methods (1)(2)(3) of Example 1.

[0180] In the present embodiment, phenoxy resin (also known as polyphenoloxy resin) is used to replace epoxy resin. No catalyst is needed and the material is directly mixed with titanium hydride for mechanical chemical ball milling reaction. The obtained product is hydroxy nano-organic titanium polymer TPP-2.

[0181] The reaction process is as follows:

[0182]

[0183] Although the raw material formulas of Examples 4 and 5 are slightly different, the polymerization products are the same, both of which are hydroxy nano-organic titanium polymer TPP-2. The only difference is that the molecular weight of the former is smaller than that of the latter, which can be distinguished from the viscosity of the product. The latter is superior to the former in terms of performance.

[0184] The method for identifying two nano-organic titanium polymers, TPP-1 of Examples 1 to 3 and TPP-2 of Examples 4 to 5, is as follows: After the TPP-1 polymer is mixed with a polyamine epoxy curing agent, it is completely cured within 2 hours at room temperature; when the TPP-2 polymer is mixed with a polyamine epoxy curing agent, no cross-linking reaction occurs, indicating that the TPP-2 polymer does not contain epoxy groups. Conversely, after the TPP-2 polymer is mixed with an isocyanate curing agent, it is completely cured within 2 hours at room temperature; and when the TPP-1 polymer is mixed with an isocyanate curing agent, no cross-linking reaction occurs, indicating that the TPP-1 polymer does not contain -OH groups.

[0185] The synthetic products of the above Examples 1 to 5 are all nano-organic titanium polymers, among which Examples 1 to 3 are epoxy-based nano-organic titanium polymers, and Examples 4 to 5 are hydroxyl-based nano-organic titanium polymers.

[0186] The physical properties of the nano-organic titanium polymer prepared above were tested, and the test results are listed in Table 1.

[0187] Table 1 Technical indicators of nano-organic titanium polymers

[0188]

[0189] (III) Synthesis of titanium-based polymer alloy copolymers by mechanochemical method

[0190] Example 6

[0191] Synthesize titanium-based polyarylethersulfoneketone copolymer or titanium-based polyarylethernitrileketone by mechanochemical method:

[0192] (1) Preparation of 40% phthalazine poly(arylethersulfoneketone) (PPESK) or 40% phthalazine poly(arylethernitrileketone) (PPENK):

[0193] Take 100 parts of raw materials N-methylpyrrolidone (NMP), 150 parts of N,N-dimethylacetamide (DMA), 350 parts of N,N-dimethylformamide (DMF), 400 parts of SK-2 poly(arylethersulfoneketone) (PPESK) or poly(arylethernitrileketone) (PPENK), put them into a dissolving kettle and heat-dissolve them at 80°C until they are completely dissolved (clear and transparent), and then discharge the materials to obtain 40% PPESK resin liquid or 40% PPENK for standby use.

[0194] (2) Weigh four grinding balls of different particle size distribution (which can be zirconium balls or 316L stainless steel balls) by weight and put them into a planetary ball mill reactor. The particle sizes of the grinding balls are Φ20 mm, Φ15 mm, Φ10 mm, and Φ5 mm, respectively, and the mass ratio is 10:20:30:40;

[0195] (3) Take 600 parts of hydroxy nano-organic titanium polymer (TPP-2), 400 parts of 40% PPESK or 40% PPENK resin solution reserved in (1), and 5 parts of Ziegler-Natta catalyst, mix and disperse them uniformly, and inject them into a planetary ball mill reactor with a ball to material mass ratio of 2:1. The reactor top cover 3 is tightened and sealed with bolts;

[0196] (4) Start the planetary ball mill reactor power switch 2, the ball mill reaction time is 6 hours, the temperature in the reactor reaches 120°C, the reactor is stopped, the temperature is kept for 1 hour, and the product is titanium-based polyarylethersulfoneketone copolymer or titanium-based polyaryletheracetoneketone copolymer. The copolymer is in a homogeneous state, the viscosity (25°C) is 8000-10000mPa·s, the solid content (wt%) is>80%, and there is no sedimentation after storage for 12 months.

[0197] The chemical reaction process of synthesizing titanium-based polyarylethersulfoneketone copolymer using TPP-2 and PPESK is expressed by the following equation:

[0198]

[0199] The reaction process of synthesizing titanium-based polyarylether nitrile ketone copolymer using TPP-2 and PPENK is as follows:

[0200]

[0201]

[0202] Example 7

[0203] Synthesis of titanium-based polyamide-imide copolymers by mechanochemical method:

[0204] (1) Preparation of 40% soluble polyamide-imide: 100 parts of N-methylpyrrolidone (NMP), 150 parts of N,N-dimethylacetamide (DMA), 350 parts of N,N-dimethylformamide (DMF), and 400 parts of PAI-10 soluble polyamide-imide (PAI) are placed in a dissolving kettle and heated to 80°C until completely dissolved (clear and transparent), and then the material is discharged to obtain a 40% PAI resin solution for use.

[0205] (2) Weigh four grinding balls of different particle size distribution (which can be zirconium balls or 316L stainless steel balls) by weight and put them into a planetary ball mill reactor. The particle sizes of the grinding balls are Φ20 mm, Φ15 mm, Φ10 mm, and Φ5 mm, respectively, and the mass ratio is 10:20:30:40;

[0206] (3) 600 parts of hydroxy nano-organic titanium precursor (TPP-2) and 400 parts of 40% PAI resin liquid are taken, and the Ziegler-Natta catalyst is not selected. The TPP-2 and 40% PAI resin liquid are evenly blended and dispersed, and injected into a planetary ball mill reactor, with a ball:material mass ratio of 2:1. The synthesis preparation is carried out by using an ultrasonic generator to assist the high-energy ball mill reactor, and the reactor top cover 3 is tightened and sealed with bolts;

[0207] (3) Start the planetary ball milling reactor power switch and ultrasonic generator switch, the ultrasonic ball milling reaction time is 3 hours, when the temperature in the reactor reaches 160°C, stop the reactor, keep warm for 1 hour, and discharge the product, which is a titanium-based polyamide-imide copolymer. The copolymer is in a homogeneous state, the test viscosity (25°C) is 6000-8000mPa·s, the solid content (wt%) is>80%, there is no sedimentation after storage for 12 months, and the viscosity of the system does not thicken.

[0208] The mechanical chemical synthesis of titanium-based polyamide-imide copolymers has the following reaction process:

[0209]

[0210] The synthetic products of Examples 6 to 7 are all titanium-based polymer alloy copolymers, among which Example 6 is a titanium-based polyarylethersulfoneketone copolymer or a titanium-based polyarylethernitrileketone copolymer, and Example 7 is a titanium-based polyamideimide copolymer. The technical performance indicators after testing are shown in Table 2.

[0211] Table 2 Technical performance indicators of titanium-based polymer alloy copolymers

[0212]

[0213]

[0214] (IV) Application of Nano-organic Titanium Polymers and Titanium-based Polymer Alloy Copolymers

[0215] The following examples 8-12 are examples of making coatings using nano-organic titanium polymers

[0216] Example 8

[0217] A two-component solvent-free nano-organic titanium heavy-duty anti-corrosion coating, which is divided into a primer, an intermediate paint and a topcoat. The specific implementation technical scheme is as follows:

[0218] (1) Primer manufacturing method:

[0219] ① Raw material composition of component A (by mass): 15 parts of TPP-1 nano-organic titanium polymer, 30 parts of EP127 epoxy resin, 5 parts of 692 epoxy active dilution, 5 parts of 20% graphene dispersion slurry, 1 part of FR-0516 dispersant, 1 part of F-118 anti-settling agent, 1 part of A630-20X polyamide wax slurry, 0.5 parts of BYK-052 defoamer, 0.5 parts of BYK-306 leveling agent, 3 parts of PB-70 polyphosphate, 1 part of KH-550 coupling agent, 1 part of SD-1 organic bentonite, 1 part of R974 fumed silica, and 35 parts of 1000 mesh ultrafine zinc powder.

[0220] ② Component B is solvent-free epoxy curing agent: 5.0 parts of MH-219 epoxy curing agent and 5.0 parts of MH-112 epoxy curing agent, mixed in equal amounts.

[0221] The mass ratio of group A to group B is 10:1 (wt).

[0222] (2) Method for manufacturing intermediate paint:

[0223] ① Raw material composition of component A (by mass): 15 parts of TPP-1 nano-organic titanium polymer, 35 parts of EP128 epoxy resin, 8 parts of 692 epoxy reactive diluent, 30 parts of 400 mesh mica red iron oxide, 1 part of FR-0516 dispersant, 0.5 parts of BYK-052 defoamer, 0.5 parts of BYK-306 leveling agent, 1.5 parts of A630-20X polyamide wax slurry, 1 part of SD-2 organic bentonite, 5 parts of PB-70 polyphosphate, 1.5 parts of ZJ-401 titanate coupling agent, and 1 part of R974 fumed silica.

[0224] ② Component B is solvent-free epoxy curing agent: 5.0 parts of MH-219 epoxy curing agent and 5.0 parts of MH-112 epoxy curing agent, mixed in equal amounts.

[0225] The mass ratio of group A to group B is 10:1 (wt).

[0226] (3) Method for manufacturing topcoat:

[0227] ① Raw material composition of component A (in parts by mass): 25 parts of TPP-1 nano-organic titanium polymer, 35 parts of DEN-431 phenolic epoxy resin, 5 parts of 692 epoxy reactive diluent, 5 parts of AM-100 pigment carbon black, 10 parts of 1250 mesh mica powder, 5 parts of 20% graphene dispersion slurry (self-made), 1 part of FR-0516 wetting and dispersing agent, 1 part of F-118 anti-settling agent, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoaming agent, 0.5 parts of BYK-306 leveling agent, 2 parts of ZJ-401 titanate coupling agent, 8 parts of NBR-1704 liquid nitrile rubber, and 1 part of R974 fumed silica.

[0228] ② Component B is solvent-free epoxy curing agent: 10 parts of MH-219 epoxy curing agent and 10 parts of MH-112 epoxy curing agent, mixed in equal amounts.

[0229] The mass ratio of group A to group B is 5:1 (wt).

[0230] The coating process and manufacturing technology are carried out in the following steps:

[0231] (1) Preparation of component A: Weigh each raw material by mass, use a high-speed disperser to shear and disperse for 20 min, then grind it in a basket sand mill equipped with zirconium beads to a particle size of ≤20 μm, and pack it;

[0232] (2) Preparation of component B: Mix and disperse the above two epoxy curing agents evenly and package them separately.

[0233] This formula technology product is mainly used for heavy-duty anti-corrosion coating inside equipment and facilities in working environments with normal temperature or not exceeding 120°C. Its supporting composite coating has excellent performance, which is 2 to 3 times the service life of the supporting composite coating system of traditional epoxy anti-corrosion coating and vinyl ester anti-corrosion coating. Its tested technical indicators are shown in Table 3.

[0234] Example 9

[0235] A nano-organic titanium oil-resistant, static-conducting, heavy-duty anti-corrosion coating for oil tanks and oil pipelines, which is divided into a primer and a topcoat. The specific technical implementation scheme is as follows:

[0236] (1) Primer manufacturing method:

[0237] ① Raw material composition of component A (by mass): 15 parts of TPP-1 nano-organic titanium polymer, 30 parts of EP127 epoxy resin, 5 parts of 692 epoxy active dilution, 5 parts of 20% graphene dispersion slurry, 1 part of FR-0516 dispersant, 1 part of F-118 anti-settling agent, 1 part of A630-20X polyamide wax slurry, 0.5 parts of BYK-052 defoamer, 0.5 parts of BYK-306 leveling agent, 3 parts of PB-70 polyphosphate, 1 part of KH-550 coupling agent, 1 part of SD-1 organic bentonite, 1 part of R974 fumed silica, and 35 parts of 1000 mesh ultrafine zinc powder.

[0238] ② Component B is solvent-free epoxy curing agent: 5.0 parts of MH-219 epoxy curing agent and 5.0 parts of MH-112 epoxy curing agent, mixed in equal amounts.

[0239] The mass ratio of group A to group B is 10:1 (wt).

[0240] (2) Method for manufacturing topcoat:

[0241] ① Raw material composition of component A (in parts by mass): 20 parts of TPP-1 nano-organic titanium polymer, 30 parts of DEN-431 phenolic epoxy resin, 5 parts of 692 epoxy reactive diluent, 20 parts of A868 anatase titanium dioxide, 5 parts of 1250 mesh mica powder, 5 parts of 10% graphene dispersion slurry, 1 part of FR-0516 wetting and dispersing agent, 1 part of F-118 anti-settling agent, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoaming agent, 0.5 parts of BYK-306 leveling agent, 2 parts of ZJ-401 titanate coupling agent, 8 parts of NBR-1704 liquid nitrile rubber, and 1 part of R974 fumed silica.

[0242] ② Component B is solvent-free epoxy curing agent: 12 parts of H-160 aromatic amine low viscosity solvent-free epoxy curing agent and 8 parts of VT6034 low viscosity solvent-free polyamide epoxy curing agent, mix evenly.

[0243] The mass ratio of group A to group B is 5:1 (wt).

[0244] Coating process and manufacturing method:

[0245] (1) Preparation of component A: Weigh each raw material by mass, use a high-speed disperser to shear and disperse for 30 min, then grind it in a basket sand mill equipped with zirconium beads to a particle size of ≤20 μm, and pack it;

[0246] (2) Preparation of component B: Mix and disperse the above two epoxy curing agents evenly and then package them.

[0247] The performance test of this group of coatings shall comply with the technical indicators of primer and topcoat in Table 3.

[0248] Table 3 Technical performance indicators of nano-organic titanium heavy-duty anti-corrosion coatings

[0249]

[0250]

[0251] Example 10

[0252] A nano-organic titanium two-component heavy-duty anti-corrosion coating resistant to high temperature and acidic environment corrosion, which is divided into a primer and a topcoat. The specific implementation technical scheme is as follows:

[0253] (1) Primer manufacturing method:

[0254] ① Raw material composition of component A (by mass): 20 parts of TPP-2 nano-organic titanium polymer, 5 parts of ALT-202 bisoxazolidine, 15 parts of 40% YP-50S phenoxy resin liquid, 15 parts of 50% 609 epoxy resin liquid, 5 parts of D670 elastic polyester resin, 10 parts of 50% 2402 phenolic resin liquid, 5 parts of 20% graphene dispersion slurry, 15 parts of ZP-08 aluminum zinc phosphate anti-rust pigment, 5 parts of 1250 mesh mica powder, 1 part of FR-0516 wetting and dispersing agent, 1 part of F118 anti-settling agent, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoaming agent, 0.5 parts of BYK-306 leveling agent, and 1 part of Y200 fumed silica.

[0255] ② Component B is solvent-free isocyanate curing agent: 20 parts of HT-100HDI curing agent.

[0256] The weight ratio of group A to group B is 5:1 (wt).

[0257] (2) Method for manufacturing topcoat:

[0258] ① Raw material composition of component A (in parts by mass): 30 parts of TPP-2 nano-organic titanium polymer, 5 parts of ALT-202 bisoxazolidine, 15 parts of 40% YP-50S phenoxy resin liquid, 15 parts of 50% 609 epoxy resin liquid, 5 parts of D670 elastic polyester resin, 10 parts of 50% 2402 phenolic resin liquid, 5 parts of 20% graphene dispersion slurry, 5 parts of MA-100 Mitsubishi pigment carbon black, 5 parts of 1250 mesh mica powder, 1 part of FR-0516 wetting and dispersing agent, 1 part of F118 anti-settling agent, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoaming agent, 0.5 parts of BYK-306 leveling agent, and 1 part of Y200 fumed silica.

[0259] ② Component B is solvent-free isocyanate curing agent: 25 parts of HT-100HDI curing agent.

[0260] Among them, the mass ratio of group A and group B is 4:1.

[0261] Coating process and manufacturing technology:

[0262] (1) Preparation of component A: Weigh each raw material by mass, use a high-speed disperser to shear and disperse for 25 min, then grind it in a basket sand mill equipped with zirconium beads to a particle size of ≤20 μm, and pack it;

[0263] (2) Preparation of component B: Mix and disperse the above two epoxy curing agents evenly and then package them.

[0264] This formula technology product is mainly used for heavy-duty anti-corrosion coating inside and outside equipment facilities under medium and high temperature (120-250℃) working conditions, and is widely used in heavy-duty anti-corrosion coating protection of desulfurization equipment systems such as thermal power plants, coal chemical industry, steel and non-ferrous metal smelting. Its technical performance indicators after testing are shown in Table 4.

[0265] Table 4 Technical performance indicators of titanium-based graphene polymer alloy heavy-duty anti-corrosion coatings

[0266]

[0267]

[0268] *Solid content is the measured value after mixing A / B components.

[0269] Embodiment 11

[0270] A nano-organic titanium marine heavy-duty anti-corrosion coating specially used for offshore oil platforms, wind power towers and photovoltaic brackets, which is divided into a primer and a topcoat; both the primer and the topcoat are composed of two components. The specific implementation technical scheme is as follows:

[0271] (1) Primer manufacturing method:

[0272] ① Raw material composition of component A (in parts by mass): 15 parts of TPP-1 nano-organic titanium polymer, 28 parts of EP127 epoxy resin, 5 parts of 692 epoxy active dilution, 5 parts of 20% graphene dispersion slurry (self-made), 1 part of FR-0516 dispersant, 1 part of F-118 anti-settling agent, 1 part of A630-20X polyamide wax slurry, 0.5 parts of BYK-052 defoamer, 0.5 parts of BYK-306 leveling agent, 5 parts of LNBR-26 liquid nitrile rubber, 1 part of KH-550 coupling agent, 1 part of SD-1 organic bentonite, 1 part of R974 fumed silica, and 35 parts of F100 flake zinc powder.

[0273] Mix and disperse the above components evenly, and then pack them without grinding.

[0274] ② Component B is solvent-free epoxy curing agent: 5.0 parts of MH-219 epoxy curing agent and 5.0 parts of MH-112 epoxy curing agent, mixed in equal amounts.

[0275] The weight ratio of group A to group B is 5:1 (wt).

[0276] This coating is a solvent-free product and can also be used as a cold-coated zinc coating to replace chemical galvanizing and hot-dip galvanizing.

[0277] (2) Method for manufacturing topcoat:

[0278] ① Raw material composition of component A (in parts by mass): 20 parts of TPP-2 nano-organic titanium polymer, 5 parts of ALT-202 bisoxazolidine, 40 parts of WB1500-80 acrylic polysiloxane resin, 5 parts of D670 elastic polyester resin, 5 parts of 20% graphene dispersion slurry, 20 parts of R706 rutile titanium dioxide, 1 part of FR-0516 wetting and dispersing agent, 1 part of F118 anti-settling agent, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoaming agent, 0.5 parts of BYK-306 leveling agent, and 1 part of Y200 fumed silica.

[0279] ② Component B is solvent-free isocyanate curing agent: 20 parts of HT-100HDI curing agent.

[0280] Among them, the mass ratio of group A and group B is 5:1.

[0281] This product is mainly used for heavy-duty anti-corrosion coating on the surface of steel structures in marine environments, such as offshore cross-sea bridges, oil platforms, offshore wind power towers, offshore photovoltaic brackets, etc. The product technical performance indicators are shown in Table 5.

[0282] Table 5 Technical performance indicators of nano-organic titanium marine heavy-duty anti-corrosion coatings

[0283]

[0284]

[0285] Example 12

[0286] A cathodic protection weld putty for preventing electrochemical corrosion of metal structure welds, which is divided into a primer and a topcoat. The specific implementation technical scheme is as follows:

[0287] The raw material composition of component A (by mass): 15 parts of TPP-2 nano-organic titanium polymer, 5 parts of ALT-202 bisoxazolidine, 10 parts of 40% YP-50S phenoxy resin liquid, 10 parts of 50% 609 epoxy resin liquid, 5 parts of D670 elastic polyester resin, 10 parts of 20% graphene dispersion slurry, 1 part of Y200 fumed silica, 1 part of FR-0516 wetting dispersant, 1 part of F118 anti-settling agent, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoamer, 0.5 parts of BYK-306 leveling agent, 40 parts of D300 flaky zinc powder. Directly mix the above materials, disperse and stir them evenly, and then pack them.

[0288] Component B is solvent-free isocyanate curing agent: 10 parts of HT-100HDI curing agent.

[0289] The mass ratio of group A to group B is 10:1 (wt).

[0290] This putty is an additional product for heavy-duty anti-corrosion coating of metal steel components, which mainly solves the problem of electrochemical corrosion at welds. Since the metal material of the steel structure is different from that of the welding rod, a potential difference will be formed between the weld and the metal ends of the structure after electric welding, which is what people in the industry often call a corrosion galvanic cell. Once a corrosion galvanic cell is formed, electrochemical corrosion will occur regardless of whether you apply anti-corrosion coating protection, because this corrosion starts from the inside of the metal. The working principle of cathodic protection putty is that the putty protective layer acts as a sacrificial anode (metal zinc), and graphene plays the role of a conductive agent. It is released in the putty layer to form a conductive network, so that the potential difference of the galvanic cell tends to balance, which plays a role in cathodic protection. The technical performance indicators of titanium-based graphene polymer alloy cathodic protection weld putty are shown in Table 6.

[0291] Table 6 Technical performance indicators of titanium-based polymer alloy cathodic protection weld putty

[0292]

[0293]

[0294] The following examples 13-14 are examples of making coatings from titanium-based polymer alloy copolymers

[0295] Example 13

[0296] A single-component high-temperature acid corrosion-resistant oil well pipe coating, which is divided into special coatings for shallow oil and gas fields and deep oil and gas fields, and is divided into primer and topcoat.

[0297] (1) A method for manufacturing a titanium-based polymer alloy coating for shallow oil and gas field well pipes. The specific technical implementation scheme is as follows:

[0298] ① Raw material composition of primer (by mass): 15 parts of titanium-based polyamide-imide copolymer (TPAI), 15 parts of 40% YP-50S phenoxy resin liquid, 15 parts of 50% 609 epoxy resin liquid, 6 parts of D670 elastic polyester resin, 16 parts of ZP-20 zinc phosphate anti-rust pigment, 1 part of FR-0516 wetting and dispersing agent, 1 part of F118 anti-settling agent, 0.5 parts of BYK-052 defoaming agent, 0.5 parts of BYK-306 leveling agent, 1 part of SD-1 organic bentonite, 1 part of Y200 fumed silica, 5 parts of N-methylpyrrolidone (NMP), 10 parts of N,N-dimethylacetamide (DMA), 3 parts of dapsone (DDS) latent curing agent, B1358 / 100 blocked cycloaliphatic polyisocyanate 10 parts.

[0299] ② Raw material composition of topcoat (by mass): 20 parts of titanium-based polyamide-imide copolymer (TPAI), 15 parts of 40% YP-50S phenoxy resin liquid, 10 parts of 50% 609 epoxy resin liquid, 5 parts of D670 elastic polyester resin, 4 parts of MA-100 Mitsubishi carbon black pigment, 8 parts of 1250 mesh mica powder, 1 part of FR-0516 wetting and dispersing agent, 1 part of F118 anti-settling agent, 1 part of Y200 fumed silica, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoamer, 0.5 parts of BYK-306 leveling agent, 6 parts of N-methylpyrrolidone (NMP), 14 parts of N,N-dimethylacetamide (DMA), 3 parts of dapsone (DDS) latent curing agent, B1358 / 100 blocked cycloaliphatic polyisocyanate 10 parts.

[0300] The coating process and manufacturing technology are carried out in the following steps:

[0301] Weigh each raw material by mass, use a high-speed disperser to shear and disperse for 20 minutes, then grind it in a basket sand mill equipped with zirconium beads to a particle size of ≤20 μm and bag it.

[0302] (2) A method for manufacturing a titanium-based polymer alloy coating for deep oil and gas field well pipes. The specific technical implementation scheme is as follows:

[0303] ① Raw material composition of primer (by mass): 15 parts of titanium-based polyarylethersulfoneketone copolymer (TPESK), 10 parts of 40% YP-50S phenoxy resin liquid, 10 parts of 50% 609 epoxy resin liquid, 6 parts of D670 elastic polyester resin, 1 part of FR-0516 wetting and dispersing agent, 1 part of F118 anti-settling agent, 0.5 parts of BYK-052 defoaming agent, 0.5 parts of BYK-306 leveling agent, 1 part of SD-1 organic bentonite, 1 part of Y200 fumed silica, 3 parts of N-methylpyrrolidone (NMP), 8 parts of N,N-dimethylacetamide (DMA), 3 parts of dapsone (DDS) latent curing agent, B1358 / 100 blocked cycloaliphatic polyisocyanate 10 parts, D300 flake zinc (D 50 =4~5μm) 30 parts.

[0304] ② Raw material composition of topcoat (by mass): 20 parts of titanium-based polyarylethersulfoneketone (TPESK), 15 parts of 40% YP-50S phenoxy resin liquid, 10 parts of 50% 609 epoxy resin liquid, 7 parts of D670 elastic polyester resin, 5 parts of MA-100 Mitsubishi carbon black pigment, 10 parts of 1250 mesh mica powder, 1 part of FR-0516 wetting and dispersing agent, 1 part of F118 anti-settling agent, 1 part of Y200 fumed silica, 1 part of SD-1 organic bentonite, 0.5 parts of BYK-052 defoamer, 0.5 parts of BYK-306 leveling agent, 5 parts of N-methylpyrrolidone (NMP), 10 parts of N,N-dimethylacetamide (DMA), 3 parts of dapsone (DDS) latent curing agent, B1358 / 100 blocked cycloaliphatic polyisocyanate 10 parts.

[0305] The coating process and manufacturing technology are carried out in the following steps:

[0306] Each raw material was weighed by mass, sheared and dispersed using a high-speed disperser for 30 minutes, then ground in a basket sand mill equipped with zirconium beads to a particle size of ≤20 μm, and bagged.

[0307] This coating is only suitable for use on automated coating production lines. The coating process requires sandblasting (or shot blasting) inside and outside the steel pipe, the cleaning level is required to reach ISO Sa2.5, and the roughness is required to be ≥40μm. After automatically spraying the first primer, the wet film thickness is required to reach 120-140μm, and the drying temperature is set at 120℃ when entering the oven for 15-20 minutes. The purpose is to evaporate the solvent. At this time, the paint film is not really cured (called false drying), and then enter the next coating of the second primer; according to this process, two primers and two topcoats are applied, and the last topcoat is dried at 200℃ for 30 minutes or 220℃ for 20 minutes. At this time, the paint film is completely cross-linked and cured, and the total dry film thickness is required to reach 180-200μm.

[0308] The technical performance indicators of special coatings for oil well pipes after testing are shown in Table 7.

[0309] Table 7 Technical performance indicators of titanium-based polymer alloy oil well pipe special coating

[0310]

[0311]

[0312] Note: The above inspection standards comply with ZY / T0544 Technical Conditions for Internal Coatings of Petroleum Drill Pipes and SY / T6717-2016 Technical Conditions for Internal Coatings of Oil Pipes and Casings.

[0313] Embodiment 14

[0314] A method for manufacturing a solvent-free sealant coating (abbreviated as A / B glue) for oil well pipe joint (coupling) threads, the specific technical implementation scheme is as follows:

[0315] The raw material composition of Group A (in parts by mass): 15 parts of titanium-based polyarylether nitrile ketone copolymer (TPENK), 35 parts of TPP-2 nano-organic titanium polymer, 20 parts of RFS-1505 liquid fluorosilicone rubber, 27 parts of 5000 mesh barium sulfate powder, 0.5 parts of FR-0516 wetting and dispersing agent, 0.5 parts of BYK-052 defoaming agent, 1 part of SD-1 organic bentonite, and 1 part of Y200 fumed silica.

[0316] The production process adopts three-roller rolling and is packaged in 800g 1L tinplate cans.

[0317] Group B: directly pack 200g of HT-100HDI trimer curing agent into 0.3L tinplate cans.

[0318] The ratio of A / B glue is 4:1 (wt). When used on site, open the A / B group tank cover, pour the B group curing agent into the A group, stir evenly with a stick, and apply it to the inner thread of the oil well pipe hoop and the outer thread of the well pipe joint to connect the pipe hoop and the pipe joint. After mechanical tightening, the sealant will cure and seal within 2 hours. This product is a sealing material for on-site downhole operations to match the inner coating of oil and gas field well pipes, which can prevent the corrosion of the inner thread of the oil well pipe hoop.

[0319] Its technical performance indicators are shown in Table 8.

[0320] Table 8 Technical indicators of titanium-based polymer alloy oil well pipe coupling thread sealant coating

[0321]

[0322] The above embodiments 1 to 14 are only further deepening and supporting the essential content of the present invention. After reading this specification, ordinary technicians in the relevant field can understand the specific implementation method of the present invention. However, no matter how others modify or tamper with it, it does not deviate from the technical scope of the present invention and is subject to the scope of protection of the present invention.

Claims

1. A method for preparing a nano-organic titanium polymer, characterized in that: The raw materials and weight parts are: 50-200 parts of organic synthetic resin; 200-400 parts of organic synthetic resin diluent; 500-800 parts of titanium hydride powder; 50-150 parts of nano material dispersant; 20-50 parts of polymer toughening agent; 5-20 parts of coupling agent; 1-10 parts of functional auxiliary agent; and 0-10 parts of gamma-phase nano alumina or sodium hydrogen phthalate catalyst.

2. The method for preparing a nano-organic titanium polymer according to claim 1, characterized in that: The organic synthetic resin is a liquid low-viscosity epoxy resin; the organic synthetic resin diluent is an epoxy reactive diluent including: a multifunctional glycidyl ether or an ester reactive solvent.

3. The method for preparing a nano-organic titanium polymer according to claim 1, characterized in that: The organic synthetic resin is a phenoxy resin; and the organic synthetic resin diluent is a phenoxy active diluent.

4. The method for preparing a nano-organic titanium polymer according to claim 1, characterized in that: The titanium hydride powder has a purity of ≥99.5% and an average particle size of ≤10 μm.

5. The method for preparing a nano-organic titanium polymer according to claim 1, characterized in that: The nano material dispersant is a small molecule carboxyl oligomer in the form of powder or liquid.

6. The method for preparing a nano-organic titanium polymer according to claim 1, characterized in that: The polymer toughening agent is liquid rubber, organic elastomer resin or polyphosphate.

7. The method for preparing a nano-organic titanium polymer according to claim 1, characterized in that: The coupling agent is silane, titanate, aluminate or zirconate.

8. The method for preparing nano-organic titanium polymer according to claim 1, characterized in that: The functional additives include: defoamers, leveling agents, anti-settling agents, thickeners or silicone, acrylic acid, polyurethane additives.

9. The method for preparing a nano-organic titanium polymer according to claim 1, characterized in that: The purity of the γ-phase nano-alumina catalyst is ≥99.5%, and the average particle size is between 10 and 20 nm.

10. The method for preparing the nano-organic titanium polymer according to any one of claims 1 to 9, characterized in that The following steps are involved: Step 1: Add four kinds of graded grinding balls into a planetary ball mill, namely Φ20mm, Φ15mm, Φ10mm, and Φ5mm, with a mass ratio of 10-20:15-25:20-30:25-40; Step 2: Weigh each raw material component according to the raw material and weight, then mix and disperse the raw materials evenly and put them into a ball mill; Step 3: Start the ball mill, stop the machine every 1 hour at the beginning, open the top cover of the machine, exhaust once, close it and run it again, run it for 3 hours, exhaust it three times; then, continue to run it for 3-7 hours, and stop when the temperature in the reactor reaches 160-180°C and the pressure reaches 0.6-0.8MPa; Step 4: cooling and depressurizing, after the ball mill kettle is naturally cooled to room temperature, the obtained product is a nano-organic titanium polymer; In the steps 1 and 2, the ratio of the total weight of the raw materials to the total weight of the grinding balls is 1:2-5.

11. The method for preparing a nano-organic titanium polymer according to any one of claims 1 to 10, characterized in that: Liquid low-viscosity epoxy resin is used as the organic synthetic resin, epoxy reactive diluent is used as the organic synthetic resin diluent, γ-phase nano-alumina or sodium hydrogen phthalate is used as the catalyst, and other raw materials are as listed above. The generated nano-organic titanium polymer is an epoxy nano-organic titanium polymer or a hydroxy nano-organic titanium polymer. When phenoxy resin is used as the organic synthetic resin, phenoxy reactive diluent is used as the organic synthetic resin diluent, the amount of catalyst is 0, and other raw materials are as listed above, the generated nano-organic titanium polymer is a hydroxy nano-organic titanium polymer.

12. A method for preparing a coating using a nano-organic titanium polymer, characterized in that It is composed of component A and component B: Component A includes: nano-organic titanium polymer, auxiliary film-forming material, active diluent, anti-rust pigment, body pigment, dispersant, anti-settling agent, thickener, defoamer, leveling agent, coupling agent, toughening agent, thixotropic agent; Component B includes: polyamine and modified amine epoxy curing agent or aliphatic polyisocyanate curing agent.

13. The method for preparing a coating using a nano-organic titanium polymer as claimed in claim 12, characterized in that The mixing mass ratio of the nano-organic titanium polymer, auxiliary film-forming material, active diluent, anti-rust pigment, body pigment, dispersant, anti-settling agent, thickener, defoamer, leveling agent, coupling agent, toughening agent and thixotropic agent is: 5-20:25-30:5-10:20-30:10-20:0.5-1.0:0.5-1.5:0.5-2.0:0.1-1.0:0.1-1.0:0.5-2.5:3-10:0.5-2.

14. The method for preparing coating using nano-organic titanium polymer according to claim 12, characterized in that The nano-organic titanium polymer is an epoxy-based nano-organic titanium polymer or a hydroxyl-based nano-organic titanium polymer; the auxiliary film-forming material includes: phenoxy resin or epoxy resin or phenolic resin or polyurethane resin; the active diluent includes: epoxy active diluent or phenoxy active diluent or polyurethane active diluent; the anti-rust pigment includes: metal anti-rust pigment, inorganic phosphate, chromate, titanate; the body pigment includes: metal oxide and inorganic salt; the polyamine and modified amine epoxy curing agent is a solvent-free polyamine epoxy curing agent; the aliphatic polyisocyanate curing agent is a solvent-free HDI trimer curing agent.

15. The method for preparing a coating using a nano-organic titanium polymer according to any one of claims 12 to 14, characterized in that The production steps are as follows: Preparation of component A: Weigh each material according to the raw material and mass, use a shearing machine to shear and disperse for 20 to 30 minutes, then grind it in a basket sand mill equipped with grinding beads to a particle size of ≤20μm, and pack it; Preparation of component B: Mix and disperse the curing agent evenly and pack it; When in use, the coating is obtained by mixing component A and component B evenly, and the mixing mass ratio thereof is 4 to 10:

1.

16. A titanium-based polymer alloy copolymer made using nano-organic titanium polymer, characterized in that The chemical structure is as follows: Titanium-based poly(arylethersulfoneketone) copolymer Titanium-based poly(arylether nitrile ketone) copolymer Titanium-based polyamide-imide copolymer 17. A method for preparing titanium-based polymer alloy copolymer using nano-organic titanium polymer as claimed in claim 16, characterized in that: The method comprises the following materials and steps: Raw materials: 600 parts of nano-organic titanium polymer, 400 parts of 40% polymer resin liquid, 0-5 parts of Ziegler-Natta catalyst; Production steps: Preparation of 40% polymer resin liquid: 100 parts of N-methylpyrrolidone, 150 parts of N,N-dimethylacetamide, 350 parts of N,N-dimethylformamide, 400 parts of poly(phenylene ether sulfone ketone) or poly(phenylene ether nitrile ketone) or soluble polyamide-imide, put them into a dissolving kettle for hot dissolution until they are completely dissolved, thus obtaining 40% polymer resin liquid: 40% poly(phenylene ether sulfone ketone) resin liquid or 40% poly(phenylene ether nitrile ketone) resin liquid or 40% soluble polyamide-imide resin liquid; Titanium-based polymer alloy copolymer production: Step 1, taking raw materials and blending and dispersing them uniformly; Step 2, putting the raw materials mixed and dispersed uniformly in step 1 into a ball mill reactor, and adding four graded grinding balls with a mass ratio of 10-20:15-25:20-30:25-40, with diameters of Φ20mm, Φ15mm, Φ10mm, and Φ5mm respectively; Step 3, start the ball mill reactor, run it continuously for 3-6 hours, and stop it when the temperature inside the reactor reaches 120-160°C; Step 4, keeping the temperature for 1 hour, and discharging the material, which is a titanium-based polymer alloy copolymer: a titanium-based polyarylethersulfoneketone copolymer or a titanium-based polyarylethernitrileketone copolymer or a titanium-based polyamideimide copolymer; The mass ratio of the raw material to the grinding ball in step 3 is 1:2; when step 4 is prepared by ultrasonic-assisted synthesis, 0 portions of Ziegler-Natta catalyst are taken and the process is continuously run for 3 hours.

18. A method for preparing a coating from a titanium-based polymer alloy copolymer, characterized in that: Paints are divided into special and general types: The special type is a single component, and the raw materials include: titanium-based polymer alloy copolymer, auxiliary film-forming resin, pigments and fillers, coating additives, polar solvents, and latent curing agents. The general type is a two-component product, divided into Group A and Group B, wherein: Group A raw materials include titanium-based polymer alloy copolymers, auxiliary film-forming resins, pigments and fillers, coating additives, and polar solvents; Group B raw materials include normal and high temperature curing agents.

19. The method for preparing a coating from a titanium-based polymer alloy copolymer as claimed in claim 18, characterized in that: The raw material titanium-based polymer alloy copolymer includes titanium-based polyarylether sulfone ketone copolymer, titanium-based polyarylether nitrile ketone copolymer, and titanium-based polyamide-imide copolymer; the auxiliary film-forming resin includes phenoxy resin, epoxy resin, phenolic resin, and polyurethane resin; the color filler includes anti-rust pigment and body pigment; the coating additives include wetting agent, dispersant, defoamer, leveling agent, thickener, and thixotropic agent; the polar solvent is limited to chloroform, dimethylformamide, dimethylacetamide and N-methylpyrrolidone; the latent curing agent includes dicyandiamide and its modified amine, dapsone, imidazoles, acid anhydrides, and blocked isocyanate curing agents; the normal and high temperature curing agents include polyamine and modified amine epoxy curing agents, aliphatic polyisocyanate curing agents, solvent-free HDI trimer curing agents, and solvent-free polyamine epoxy curing agents.

Citation Information

Patent Citations

  • Nano-organic titanium polyalloy polymer, coating and preparation method thereof

    CN102585236B

  • Preparation method of titanium nanometer polymer

    CN106141164A

  • Nano-titanium alloy hybrid polymers, their preparation methods, and nano-hybrid composite coatings

    CN111253835B

  • Polymeric alloy polymer, polymeric alloy coating and preparation method of polymer alloy coating

    CN107337901A

  • Preparation method of organic titanium precursor polymer TPP-II and application of organic titanium precursor polymer TPP-II in special coating

    CN108503841A

Cited By

  • High-temperature-resistant non-discoloring polyarylene ether nitrile modified ink and preparation method thereof

    CN121895805A

  • High temperature resistant non-yellowing polyarylene ether nitrile modified ink and method of making

    CN121895805B